ChemInform Abstract: Dimorphic Cerium(III) Oxoarsenate(III) Ce[AsO3]. Issue 50 (16th December 2014) - Ledderboge, Florian; Metzger, Sebastian J.; Heymann, Gunter; Huppertz, Hubert; Schleid, Thomas
Abstract Colorless single crystals of α‐PbSeO3‐type Ce[AsO3] are prepared by reaction of Ce powder and As2O3 in a CsCl flux (silica tube, 750 °C, 4 d).